Multi-parametric functional hemodynamic optimization improves postsurgical outcome after intermediate risk open gastrointestinal surgery: a randomized controlled trial - Szturz, Pavel; Folwarczny, Pavel; Kula, Roman; Neiser, Jan; Ševčík, Pavel; Benes, Jan (Minerva anestesiologica, 2019)
BACKGROUND: Perioperative goal directed therapy (pGDT) using flow monitoring has been associated with improved outcomes. However, its protocols are often based on stroke volume only: as a target for fluid loading, inotropic support and vasopressors (via mathematical coupling of systemic vascular resistance). In this trial, we have tested the multi-parametric pGDT protocol based on esophageal Doppler variables (corrected flow time, peak velocity) in intermediate-to-high risk patients undergoing gastrointestinal surgery. METHODS: Intermediate-to-high risk patients undergoing gastrointestinal surgery were randomized to standard care (control) or multi-parametric pGDT (intervention). Postoperative complications and death rate as well as hospital length of stay were assessed as primary and secondary outcomes. RESULTS: Overall, 140 patients (intervention, N.=71, and control, N.=69) were included and randomized out of 197 eligible. Higher vasoactive/inotropic drug use and lower fluid balance were observed in the intervention group leading to favorable hemodynamic profile. The pGDT intervention was associated with improved primary outcome (28 days mortality and morbidity defined as occurrence of any defined complication) - 20 patients (28.2%) versus 32 (46.4%) in the control group (P=0.036); RR 0.61 (95% CI: 0.39-0.95), P=0.03. No differences in mortality and hospital length of stay were observed between groups. CONCLUSIONS: In this monocentric trial the multi-parametric pGDT protocol based on domain specific functional hemodynamic parameters was associated with lower rate of postoperative complications in intermediate-to-high risk patients undergoing scheduled gastrointestinal procedures.
Keywords: hodnocení rizik; Female; výsledek terapie; chirurgie trávicího traktu; ženské pohlaví; EGDT; Hemodynamics; hemodynamika; lidé; pooperační komplikace; Treatment Outcome; Digestive System Surgical Procedures; Risk Assessment; prospektivní studie; Male; Postoperative Complications; Aged; Prospective Studies; Early Goal-Directed Therapy; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans